Volunteers work for lesbian, gay, bisexual, transgender, and queer rights: Motivations at a Rochester social justice organization. Issue 1 (2nd January 2016) - Gates, Trevor G.; Russell, Elizabeth B.; Gainsburg, Jeanne
ABSTRACT: The reasons volunteers contribute to lesbian, gay, bisexual, transgender, and queer (LGBTQ) social justice organizations are multifaceted and need further exploration. This pilot study ( N = 35) sought to understand volunteer motivations at a Rochester, New York social justice organization fighting for LGBTQ rights. Understanding motivations for volunteerism and volunteers' perceptions about the relative advantages and obstacles of current volunteer experiences at their agency were the primary goals of the study. The study found that these volunteers are motivated primarily by their personal values, mission of the organization, and desire to develop and maintain social relationships with the LGBTQ community. Implications for volunteer resource management and research are explored.